Edukasi Kesehatan tentang Aktivitas Fisik dalam Mengontrol Kadar Gula Darah pada Penderita DM Tipe 2 di Puskesmas Tanah Tinggi Kota Binjai Tahun 2024 - Faswita, Wirda (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Diabetes Mellitus (DM) is a dangerous disease because it can cause many complications. Physical activity is one of the important things needed for successful diabetes treatment. The Indonesian Endocrine Association stated that to successfully overcome diabetes, 4 pillars of success are needed, namely education, diet, activity and treatment (Perkeni, 2019). Physical activity must also be balanced with compliance in taking antidiabetic drugs as a form of pharmacological intervention (Prasetyani, 2017). The purpose of this activity is to provide information for DM sufferers in carrying out physical activities. This activity began with a meeting with the Head of the Health Center to apply for activity permits and conduct an assessment of DM sufferers who wanted to take part in health education, then continued with education and evaluation, namely seeing the achievements of the results of the health education carried out including the level of knowledge of attitudes, enthusiasm and KGD values ​​of the participants. The results showed that the group of DM sufferers were very enthusiastic about participating in the socialization of physical exercise in controlling blood sugar levels and were willing to carry out special group activities for DM sufferers routinely with a Good knowledge level reaching 85%.